2019
DOI: 10.1002/bab.1844
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic extraction, structural characterization, and bioactivities of nonstarch polysaccharides from red yeast rice

Abstract: Red yeast rice (RYRP) has been utilized for coloring food, brewing wine, and preserving meat, which is also used as a folk medicine for centuries. In this study, a water‐soluble nonstarch polysaccharide from RYRP was extracted by using ultrasonic‐assisted extraction method. By using the Box–Behnken design to optimize the parameters for extracting the RYRP, the maximum extraction yield (3.37 ± 0.78%) was obtained under the optimal extraction conditions as follows: ratio of water to raw material (40 mL/g), extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The highest starch extraction rate of RYR was achieved when the extraction time was 3 h and then gradually decreased again. This may be because the extraction time in a certain range can increase the starch extraction rate, but too long alkaline solution will destroy the structure of RYR starch, which is not conducive to the separation of RYR protein from RYR starch; simultaneously, the extension of the extraction time may also cause the starch to hydrolyze, thus affecting the starch yield 30 . The extraction time of 3 h was chosen, considering the starch extraction rate, as well as time and cost savings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The highest starch extraction rate of RYR was achieved when the extraction time was 3 h and then gradually decreased again. This may be because the extraction time in a certain range can increase the starch extraction rate, but too long alkaline solution will destroy the structure of RYR starch, which is not conducive to the separation of RYR protein from RYR starch; simultaneously, the extension of the extraction time may also cause the starch to hydrolyze, thus affecting the starch yield 30 . The extraction time of 3 h was chosen, considering the starch extraction rate, as well as time and cost savings.…”
Section: Resultsmentioning
confidence: 99%
“…2,3 Clinically, RYR is primarily used to strengthen the spleen and eliminate food. 4 Currently, RYR has been widely studied and developed as a nutraceutical and lipidlowering drug. 5,6 According to statistics, there are more than 100 types of nutraceuticals containing RYR in the Chinese market.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Red yeast rice (RYR) is produced from rice through fermentation by Monascus purpureus (Cicero et al., 2021; Luo et al., 2020). In East Asia, red yeast rice is a widely used food additive.…”
Section: Introductionmentioning
confidence: 99%
“…RYR is a fermented product; in our previous in vivo study indicated that, the 3.49‐kDa nonstarch polysaccharides were isolated from RYR and that it possessed the gastrointestinal‐protective effect (Luo et al., 2020). Most of the modern research into RYR focused on small molecule substances such as statins and pigments; yet, oligosaccharides extracted from medicinal foods have been proved to have many beneficial effects, which provides more evidence for further development of these substances.…”
Section: Introductionmentioning
confidence: 99%